Modeling the vertical structure of the ice shelf–ocean boundary current under supercooled condition with suspended frazil ice processes: A case study underneath the Amery Ice Shelf, East Antarctica - Cheng, Chen; Jenkins, Adrian; Wang, Zhaomin; Liu, Chengyan (Ocean Modelling, 2020)
In contrast with the severe thinning of ice shelves along the coast of West Antarctica, large ice shelves (specifically, the Filchner–Ronne and Amery Ice Shelves) with deep grounding lines gained mass during the period 1994–2012. This positive mass budget is potentially associated with the marine ice production, which originates from the supercooled Ice Shelf Water plume carrying suspended frazil ice along the ice shelf base. In addition, the outflow of this supercooled plume from beneath the ice shelf arguably exerts a significant impact on the properties of Antarctic Bottom Water, as well as its production. However, knowledge of this buoyant and supercooled shear flow is still limited, let alone its structure that is generally assumed to be vertically uniform. In this study we extended the vertical one-dimensional model of ice shelf–ocean boundary current from Jenkins (2016) by incorporating a frazil ice module and a fairly sophisticated turbulence closure (i.e., k-ε model) with the effects of density stratification. On the basis of this extended model, the study reproduced the measured thermohaline properties of a perennially-prominent supercooled ice shelf–ocean boundary current underneath the Amery Ice Shelf in East Antarctica, and conducted extensive sensitivity runs to a wide range of factors, including advection of scalar quantities, far-field geostrophic currents, basal slope, and the distribution of frazil ice crystal size. Based on the simulation results, the following conclusions can be drawn: Firstly, it can be difficult to reasonably reproduce the vertical structure of the ice shelf–ocean boundary current using a constant eddy viscosity/diffusivity near the ice shelf base. Secondly, although there are no direct observations of the size of frazil ice crystals beneath the ice shelves, the size of the finest ice crystals that play an important role in controlling the ice shelf–ocean boundary current is strongly suggested. Lastly, but most importantly, the ice shelf–ocean boundary layer response to the ...